Sosialisasi Optimalisasi Tumbuh Kembang Balita Di Posyandu Growong Kidul Juwana Kabupaten Pati - Aminatul Fatayati; Feri Catur Yuliani; Putri Kusumawati P; Rr. Erni Kusuma Putri (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Health development is part of an effort to build a whole person which is carried out through child health efforts as early as possible since the child is still in the womb. Health efforts carried out since the child is still in the womb until the first five years of life, aim to maintain their survival and improve the quality of life of children in order to achieve optimal growth and development both physically, mentally, emotionally and socially and have multiple intelligences according to their genetic potential. The growth and development of children physically, mentally, socially, emotionally are influenced by nutrition, health and education. Comprehensive and quality child growth and development guidance can be carried out through stimulation activities, early detection and intervention of deviations in the growth and development of preschool children. The Stimulation, Detection and Early Intervention of Growth and Development Program (SDIDTK). Community service activities with the title of optimizing toddler growth and development in Growong Kidul Village, Juana District, Pati Regency, Central Java, aim to provide education, especially about optimizing growth and development in toddlers. Participants in this Community service activity are parents of toddlers at the Integrated Health Post in Growong Kidul Village, Juana District, Pati Regency, Central Java. The methods used in this Community service activity include lectures, discussions, sharing experiences and problem solving. The results of implementing community service activities with planning prepared by the community service team provide information about strategies for optimizing growth and development in toddlers.